Chalcopyrite UiO-67 metal-organic framework composite for CO2 fixation as cyclic carbonates. Issue 3 (June 2022) - Helal, Aasif; Alahmari, Fatimah; Usman, Muhammad; Yamani, Zain H.
Abstract: The conversion of greenhouse gas carbon dioxide (CO2 ) into cyclic carbonates which are, used as green solvents and are considered sustainable substitution to toxic chemicals, can be a competent approach to net zero-emission. This work successfully incorporated Chalcopyrite (CuFeS2 ) in UiO-67 (University of Oslo-67) to form a composite Ch@UiO-67 using a solvothermal method. After characterization by powder X-ray diffraction (PXRD), Fourier-transform infrared spectroscopy (FT-IR), N2 adsorption isotherm, thermogravimetric analysis (TGA), X-ray photoelectron spectroscopy (XPS), Field Emission Scanning Electron Microscopy- Energy Dispersive Spectroscopy (FESEM-EDS) and Inductively coupled plasma mass spectrometry (ICP-MS), Ch@UiO-67 was tested for CO2 uptake and as a catalyst in the cycloaddition reaction of styrene epoxide (SO) with CO2 to produce cyclic carbonates, in comparison to pristine UiO-67. Ch@UiO-67 was found to be more effective as a catalyst than pristine UiO-67. This catalyst was also successful with different aromatic and aliphatic epoxides for cycloaddition with CO2 and was efficiently recycled for seven consecutive cycles without a noticeable deficit in the catalytic activity. Graphical Abstract: ga1 Highlights: We have prepared a chalcopyrite incorporated UiO-67 composite (Ch@UiO-67) by facile solvothermal method. Composite Ch@UiO-67 is as stable as UiO-67 and is a better catalyst for the conversion of epoxides to cyclic carbonates. This catalyst acts under a solvent-free condition to convert styrene oxide to its cyclic carbonate with a 93% yield. The catalyst was applicable for the conversion of a wide range of aliphatic and aromatic epoxides in good yield. The catalyst was also recyclable and can be reused for seven consecutive cycles.